2012
DOI: 10.5603/fhc.2012.0084
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of proteins in healthy and pathological human renal tissues

Abstract: Abstract:Cancer development is associated with the improper glycosylation of proteins. There are alterations in the synthesis and expression of sugar structures. These changes can be important not only in the early stages of tumour development, but also in the next stages connected with cancer invasiveness and its ability to form metastases. Oligosaccharide structures of glycans in tumours deviate from normal cells. Relatively increased degrees of branching and sialylation of N-glycans, enhanced presentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The data indicated that FUT11 was the glycosyltransferase with the highest differential expression. Previous research has found that, when compared to healthy tissue, ccRCC had a greater expression of fucose [ 38 ]. El plutona zodro et al analyzed that the upregulation of FUT11 in ccRCC may be related to the development and course of ccRCC [ 39 ].…”
Section: N-glycanmentioning
confidence: 99%
“…The data indicated that FUT11 was the glycosyltransferase with the highest differential expression. Previous research has found that, when compared to healthy tissue, ccRCC had a greater expression of fucose [ 38 ]. El plutona zodro et al analyzed that the upregulation of FUT11 in ccRCC may be related to the development and course of ccRCC [ 39 ].…”
Section: N-glycanmentioning
confidence: 99%
“…It has been observed that expression of fucosylated oligosaccharides changes in cancer and inflammation (e.g. [31]), also in ccRCC [38]; hence, detection of FUT11 upregulation in our meta-analysis and in ccRCC tumors may link FUT11 to ccRCC development and progression.…”
Section: Discussionmentioning
confidence: 62%
“…Glycosylation is increasingly implicated in cancer development and progression (Borzym-Kluczyk et al 2012; Munkley and Elliott 2016; Burchell et al 2018; Reily et al 2019), but the underlying mechanisms driving this relationship necessitate substantial additional exploration (Thomas et al 2020). Specifically, glycosyltransferases have been identified in cancer in various roles and scopes: individual GTs in individual cancer types (Miller et al 2015), individual GTs in multiple cancer types, groups of GTs in individual cancers (Carlini et al 2005; Barthel et al 2008; Gupta et al 2020), and groups of GTs in multiple cancers (Petretti et al 2000; Ashkani and Naidoo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have associated increased levels of fucose and sialic acid and increased abundance of protein sugar structures with clear cell renal cell carcinoma (ccRCC) (Borzym-Kluczyk et al 2012). Increased multi-lectin affinity chromatography (M-LAC) binding of glycoproteins and changes of plasma N-glycan levels in ccRCC suggest the presence of altered glycan structures (Gbormittah et al 2014), and fucosyltransferases FUT3 and FUT6 have been observed to have decreased transcript levels in ccRCC tissue compared to matched non-tumor tissues (Drake et al 2020).…”
Section: Survey and Enrichment Of Differentially Expressed Glycosyltransferases In Cancermentioning
confidence: 99%